LAYANAN BIMBINGAN DAN KONSELING DALAM PEMBENTUKAN KEPRIBADIAN YANG BERAKHLAKUL KARIMAH UNTUK MENANGANI PERILAKU AGRESIF PADA SISWA KELAS VIII SMP NEGERI 32 BANJARMASIN - Mahrita, Mahrita; Yuliansyah, M; Auliah, Nurul (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2018)
The background of this study is that there are still problems with the aggressive behavior of students, especially class VIII students of SMP Negeri 32 Banjarmasin. For this reason, BK needs to be handled by competent teachers according to Law No. 111 of 2014 to be able to form students into the generation of hope of the nation according to Law No. 20 of 2003. The purpose of this study is to find out the services that are carried out and find out the obstacles experienced when running a program of guidance and counseling services in the formation of a personality that has a moral character to handle students' aggressive behavior. In this study, researchers used qualitative research methods. The research subject was the teacher of BK 32 SMP Negeri Banjarmasin. Data is collected through observation, interviews, and documentation. The results of this study indicate that the guidance and counseling service program at Banjarmasin State Middle School 32 has had an impact on the formation of the personality of students who have moral character. So that individual counseling services provided by counseling teachers to students who have aggressive behavioral problems are able to make better changes in these students. Suggestions from this study are as BK teachers need to understand the root causes of each student's problem, then need to understand correctly the meaning of personality (in Islam). And the school must pay attention to the guidance and counseling program in it so that it is implemented properly. Keywords: Guidance and Counseling Services, Personality, Morals, and Aggressive Behavior